A Study Of Spiritual Struggle In Muslim Diaspora Using The Maqāṣid Al-Sharī‘Ah Approach In Sami Yusuf’s Song Lyrics - Wafiq Aziz Wardah; Tenny Sudjatnika; Nurholis (Jurnal Teologi Islam, 2025)
This study examines spiritual struggle and moral guidance among Muslim diaspora as represented in Sami Yusuf’s song lyrics using a qualitative descriptive method. As Bryman (2004:269) states, qualitative research prioritizes interpretation of textual meaning rather than quantification; therefore, this study analyzes selected lyric excerpts from Came To Me, Make Me Strong, and You through the framework of Maqāṣid al-Sharī‘ah, specifically ḥifẓ al-dīn (protection of faith), ḥifẓ al-nafs (protection of psychological well-being), and ḥifẓ al-‘aql (protection of intellect). In line with Wahid (2023), Maqāṣid provides a contextual ethical approach to contemporary challenges, while Auda emphasizes its orientation toward human welfare (maṣlaḥah). The findings show that Sami Yusuf’s lyrics portray faith restoration amid disorientation (ḥifẓ al-dīn), emotional resilience and inner healing under pressure (ḥifẓ al-nafs), and moral reasoning guided by divine orientation within ideological plurality (ḥifẓ al-‘aql). Overall, the songs function as contemporary Islamic literary texts that offer spiritual and moral guidance for Muslim diaspora navigating modern uncertainties.